Maternal verbal scaffolding: association with higher language skills for 20-month-old children with prenatal polysubstance exposure. (September 2021) - Lowe, Jean R.; Hund, Lauren; Rodriguez, Dominique E.; Qamruddin, Asma; Leeman, Lawrence; Stephen, Julia M.; Bakhireva, Ludmila N.
Abstract: Background: The number of children with prenatal polysubstance exposure is increasing. Supportive mother-child interaction is a protective factor, which can ameliorate adverse effects of prenatal polysubstance exposure on developmental outcomes. Aim: To examine the role of maternal verbal scaffolding on cognitive and language development in children with prenatal polysubstance exposure. Study design: Pregnant women were recruited, and we prospectively followed mother-child dyads to 20 months of age. This analysis included 66 dyads (33 healthy controls and 33 with prenatal polysubstance exposure). Multivariable linear regression modelling was used to examine the cross-sectional association between maternal scaffolding and Bayley Scales of Infant and Toddler Development (BSID-III) score, as well as an interaction between the study group and scaffolding score. Outcome measures: The BSID-III cognitive and language score was used. Videotaped mother-child play was coded to obtain a maternal verbal scaffolding score. Effect sizes were measured using average differences in scores between groups. Results: There was no evidence of an association between study group and maternal scaffolding scores. Children in the polysubstance exposure group had lower cognitive and language scores compared to controls, but this association was not statistically significant after controlling for maternal education. Maternal scaffolding was predictive of language scores, with scores increasing by 1.24 points on average (95% CI: 0.42, 2.06) for every 1-point increase in scaffolding score after adjustment for covariates. There was no evidence of a study group-by-scaffolding interaction with respect to the language or cognitive scores. Conclusions: Maternal scaffolding during play was associated with language development in children with and without prenatal polysubstance exposure.